Non-inclusive growth, the profit motive, and the case for inclusive business - Poblador, Niceto S. (Philippine Review of Economics, 2017)
One of the greatest anomalies of our time is the widening gap in income and wealth in most societies between the rich and privileged few, and the masses at the bottom of the social pyramid who are often mired in abject poverty. While the prevalence of poverty in the face of phenomenal growth stems largely from the state’s failure to perform its traditional functions in a manner that equalizes opportunities for all members of society, business also bears a major share of the blame for an economic system that has become increasingly non-inclusive. This article takes the position that business should take the initiative in making the modern economy more inclusive. To achieve this ideal, the traditional goal of profit maximization— or the maximization of shareholder wealth, in the case of publicly held companies—needs to be re-conceptualized in terms of creating value for all groups that contribute to the process of value creation, and not just the owners of the business. Not the least among these stakeholders in the firm are the poorest members of the community. The article concludes by urging the development and implementation of inclusive business models (IBMs), solutions that provide access to economic opportunities to low-income communities in a manner that will make businesses more viable and sustainable. A few examples of firms that have successfully adopted IBMs are discussed.